The Savvy Survey #3: Successful Sampling - Jessica L. Gouldthorpe; Glenn D. Israel (EDIS)
As part of the Savvy Survey series, this publication provides Extension faculty with an overview of topics to consider when thinking about who should be surveyed. Topics in this publication include understanding the survey population, constructing the sampling frame, recognizing who exists outside the population of interest, and defining the sample. This 5-page fact sheet also provides insight on issues such as over-coverage and error that can arise because of poor sampling procedures. Written by Glenn D. Israel and Jessica L. Gouldthorpe, and published by the UF Department of Agricultural Education and Communication, October 2013.